ENGINEERING OF ZEOLITE MINERAL WITH WET IMPREGNATION INHIBITOR METAL METHOD AS RAW MATERIAL OF ANTISEPTIC BY CONTINOUS FLOW METHOD - Estiaty, Lenny Marilyn (Jurnal Zeolit Indonesia, 2010)
Industrial minerals, such as natural zeolite can be engineered into raw materials on manufacturing of medical products, especially as an antiseptic. Zeolite with the crystal structure characteristic could be function as an antiseptic carrier and active subtances would be saved on crystal structure of zeolite which was on certain circumstances will be work or out of the frame structure. The active substances are an inhibitor metal with low concentration and could be a toxic for microbial cell plasma. The used natural zeolite as an antiseptic carrier with inhibitor metal Cu has not yet developed. In this study, antiseptic substances has made by impregnation method with flow continuously were a compound or metal substances put in crystal structure without changing the crystal structure. The impregnation conducted by purification process and modification of natural zeolite become a zeolite-H in order easily to substituted by Cu metal. The products is much metals K, Na, Ca, Mg out from zeolite making a Zeolite-H was perfect, so the planting of Cu metals was maximum. The purification, modification, and impregnation process did not change the shape of crystal zeolite, and degradation do not occur on modernite peaks so expected the characteristic from zeolite does not change so it is could be functions as antiseptic carrier. Absorption test and power test of bacterial growth was conducted to try the antiseptic substances against bacteria and fungi. The result that zeolite-Cu had been successfully made although not optimal. The absorption capacity of natural zeolite higher than the absorption capacity of zeolite-Cu, because the absorption capacity of zeolite-Cu was disrupted by entry of metal Cu. Inhibition of bacteria and fungi growth occurs more on media with addition zeolite-Cu. It was because the inhibition of zeolite-Cu already functioning.